Effect of dates of transplanting on seed quality characters of basmati rice (Oryza sativa) cultivars - U.R. KAMBLE; K.K. SINGH; P. NALLATHAMBI; A.K. SINGH; H. PATHAK; S. PANDEY; S.K. LAL (Seed Research, 2026)
A field experiment was conducted on three cultivars of basmati rice (Oryza sativa L.) viz. Pusa Basmati 1, Pusa Basmati 6 and Pusa Basmati 1121 to study the effect of different dates of transplanting on seed quality characters during kharif season (2009) at Indian Agricultural Research Institute, New Delhi. The seedlings of all three varieties were transplanted at 10 days interval starting from 1 July and up to 1 August, Pusa Basmati 1121 exhibited maximum 1,000-seed weight (29.87 g) in 1 July transplanted plot and minimum 1,000-seed weight (27.47 g) in 1 August transplanted plot. However, seed weight was drastically reduced in Pusa Basmati 6 and Pusa Basmati 1 when subjected to delayed transplanting. Pusa Basmati 1121 recorded maximum germination (94.33%), followed by Pusa Basmati 1 (86.5%) and Pusa Basmati 6 (89.83%) in 1 July transplanting. Gradual decrease in germination was observed with each delay in transplanting dates, irrespective of varieties. However, seed germination (Including fresh ungerminated/dormant seed) was higher than the Indian Minimum Seed Certification Standards (80%) in all dates of transplanting. Superior seed quality in relation to electrical conductivity was observed in early transplanting, contrary to the late transplanting. Significant reduction in seedling vigour was also recorded in 1 August, compared to 1 July transplanting. Amongst three cultivars, highest seedling vigour was observed in Pusa Basmati 1121 (2578.1), followed by Pusa Basmati 6 (2071.3) and Pusa Basmati 1 (1777.3) in early transplanting dates.